Implementasi Kebijakan Pengelolaan Sampah Berbasis Komunitas: Studi Program KangPisMan di Kecamatan Sumur Bandung Kota Bandung - Aty Susanti; Miswan Miswan; Tari Lukitasari (Fakultas Politik Pemerintahan IPDN, 2026)
Abstract This study examines the implementation of the KangPisMan (Reduce, Separate, Utilize) community-based waste management policy in Sumur Bandung District, Bandung City. The research aims to analyze the effectiveness of policy implementation and identify key factors influencing its performance within the local governance context. A qualitative descriptive approach with a phenomenological perspective was employed to explore the experiences and perceptions of stakeholders involved in the program. Data were collected through in-depth interviews, field observations, and document analysis, involving purposively selected informants, including local government officials, environmental task force members, and community activists. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, with validity ensured through triangulation.The findings reveal that the KangPisMan policy has contributed to improving public awareness and encouraging initial behavioral changes in household waste management practices, particularly in waste sorting and reduction. However, the effectiveness of policy implementation remains constrained by several factors, including low community compliance, limited infrastructure and resources, and weak enforcement mechanisms. From a policy perspective, the results highlight the interaction between policy content and implementation context as critical determinants of success.This study concludes that while the regulatory framework is adequate, strengthening community engagement, enhancing institutional capacity, and ensuring consistent policy enforcement are essential to achieve sustainable urban waste management. The findings provide practical implications for improving community-based environmental governance in urban areas. Keywords: community-based waste management, KangPisMan policy, policy implementation, public policy, urban governance